The role of eigen-stresses on apparent strength and stiffness of normal, high strength, and ultra-high performance fibre reinforced concrete - Nikhil Awasthy; Erik Schlangen; Dick Hordijk; Branko Šavija; Mladena Luković (Developments in the Built Environment, 2023)
Concrete is characterized in terms of its engineering properties, mainly strength and stiffness, which are subsequently used in structural design. However, the apparent (i.e., measured) concrete properties are not intrinsic but dependent on the conditions under which the measurement is performed. Herein a combined experimental and numerical study is performed to clarify the effects of hygral gradients and resulting eigen-stresses in self-restrained concrete on its apparent strength. Compressive strength, splitting tensile strength and Young's modulus are tested. Three mixes of varying strength grades are studied: normal strength, high strength, and ultra-high performance fibre reinforced concrete. Samples are subjected to two different curing conditions. To investigate the effect of size on the apparent properties, 50 mm, 100 mm and 150 mm cubes are tested. Depending on the size of the specimen there can be an underestimation or overestimation of up to 25% of the real concrete (e.g., splitting, direct tensile) strength.